BÚSQUEDA DE Trichinella spiralis EN CERDOS DE CRIANZA NO TECNIFICADA EN ZONAS PERIURBANAS DE LIMA, PERÚ - Arrese H., Giovanna (2014)
The aim of this study was to analyze the possible presence of Trichinella spiralis in non-technified pig farms of Lima, Peru. Samples of blood and diaphragm muscle from 185 pigs were collected from two slaughterhouses. Muscles samples were evaluated using the trichinoscopy and blood samples by the use of an indirect ELISA commercial kit to detect the presence of antibodies against T. spiralis. All samples were negative to both tests. The Monte Carlo simulation (@ Risk) showed that the probability of finding T. spiralis in Lima was 0.53%.